Differential effects of the SARS-CoV-2 pandemic on patients presenting to a neurological emergency room depending on their triage score in an area with low COVID-19 incidence - Millán, Margit; Nagel, Simon; Gumbinger, Christoph; Busetto, Loraine; Purrucker, Jan; Hametner, Christian; Ringleb, Peter A.; Mundiyanapurath, Sibu (European journal of neurology, 2021)
Background We analyzed the effects of the SARS-CoV-2 pandemic on neurologic emergencies, depending on the patients' triage score in a setting with relatively few COVID-19 cases and without lack of resources. Methods Consecutive patients of a tertiary care center with a dedicated neurologic emergency room (nER) were analyzed. The time period of the first lockdown in Germany (calendar weeks 12-17, 2020) was retrospectively compared to the corresponding period in 2019 regarding the number of patients presenting to the nER, the number of patients with specific triage scores (Heidelberg Neurological Triage Score), the number of patients with stroke, and the quality of stroke care. Results A total of 4330 patients were included. Fewer patients presented themselves in 2020 compared to 2019 (median [interquartile range] per week: 134 [118-143] vs. 187 [182-192]; p = 0.015). The median numbers of patients per week with triage 1 (emergent) and 4 (non-urgent) were comparable (51 [43-58] vs. 59 [54-62]; p = 0.132, and 10 [4-16] vs. 16 [7-18]; p = 0.310, respectively).The median number of patients per week declined in categories 2 and 3 in 2020 (41 [37-45] vs. 57 [52-61]; p = 0.004, and 28 [23-35] vs. 61 [52-63]; p = 0.002, respectively. No change was observed in the absolute number of strokes (138 in 2019 and 141 in 2020). Quality metrics of stroke revascularization therapies (symptom-to-door time, door-to-needle time or relative number of therapies) and stroke severity remained constant. Conclusion During the lockdown period in 2020, the number of patients with emergent symptoms remained constant, while fewer patients with urgent symptoms presented to the nER. This may imply behavioral changes in care-seeking behavior.